Two New Retigerane‐Type Sesterterpenoids from the Lichen Leprocaulon microscopicum. Issue 2 (February 2016) - Millot, Marion; Martin‐de‐Lassalle, Marie; Chollet‐Krugler, Marylène; Champavier, Yves; Mambu, Lengo; Chulia, José‐Albert; Lacaille‐Dubois, Marie‐Aleth
Abstract: Two new sesterterpenes, 1 and2, have been isolated from the lichen Leprocaulon microscopicum. In addition to classic chromatographic methods, a liquid‐liquid chromatography technique, namely centrifugal partition chromatography (CPC) was applied for the purification of compound2 . The structures were determined by analyses of mass spectrometry and 1D‐ and 2D‐NMR data. The relative configuration of the isolated compounds was assigned on the basis of 2D‐NOESY experiments. The two compounds possess a rare pentacyclic carbon skeleton typical for lichen metabolism, and quite unusual in the vegetal kingdom. Abstract :